2021
DOI: 10.1097/qai.0000000000002546
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mathematical Model to Estimate the Cost-Effectiveness of HRSA's Ryan White HIV/AIDS Program

Abstract: Background: The Health Resources and Services Administration's Ryan White HIV/AIDS Program provides services to more than half of all people diagnosed with HIV in the United States. We present and validate a mathematical model that can be used to estimate the long-term public health and cost impact of the federal program. Methods: We developed a stochastic, agent-based model that reflects the current HIV epidemic in the United States. The model simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…27 including processes with two infectious periods. 5,28,29 Another common epidemic process is an SEIR process. The Stages S and R still refer to Susceptible and Recovered, respectively.…”
Section: Epidemic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…27 including processes with two infectious periods. 5,28,29 Another common epidemic process is an SEIR process. The Stages S and R still refer to Susceptible and Recovered, respectively.…”
Section: Epidemic Modelmentioning
confidence: 99%
“…Specifically, we set the parameters for the exponential distributions that govern the lengths of the infectious acute and long‐term periods such that the durations have a mean of 3 months (κA=3$$ {\kappa}_A=3 $$) and 42 months (κL=42$$ {\kappa}_L=42 $$), respectively 29 . Based on existing literature, βA=0.01505$$ {\beta}_A=0.01505 $$ and βL=0.008911817$$ {\beta}_L=0.008911817 $$ 29 Simple viral evolution process: Genetic data for the pathogen consists of sequences of 1048 base pairs.…”
Section: Simulation Study: Siailr$$ S{i}^a{i}^lr $$ Epidemic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach enables us to directly input the incidence and diagnosis delay for each year. Therefore, we do not incorporate an epidemic model to simulate yearly incidence; however, our approach to assessing the CD4 model can be easily extended to these models [11][12][13]. As changes in incidence and diagnosis delay are fully integrated within the first 8 years after an intervention, results beyond this time point are not shown.…”
Section: Model Descriptionmentioning
confidence: 99%
“…And vision sensor because there are fewer pixels and low noise, high sensitivity has been occupying the mainstream market. Due to the improvement of process level and integrated circuit design technology, researchers have found that some of the shortcomings of the visual sensor can find ways to overcome and has no inherent characteristics of the visual sensor, such as high integration, small size, low power consumption, and lightweight, making the visual sensor become a hot spot for research in recent years [20].…”
mentioning
confidence: 99%